PERFORMANCE MANAGEMENT IN MULTINATIONAL COMPANIES IN AFRICA : IMPLICATIONS FOR TRANSFERABILITY OF HUMAN RESOURCE MANAGEMENT INNOVATION TO DEVELOPING COUNTRIES /: IMPLICATIONS FOR TRANSFERABILITY OF HUMAN RESOURCE MANAGEMENT INNOVATION TO DEVELOPING COUNTRIES. (May 2007) - Mamman, Aminu; Adeoye, Bolanle
No abstract available